The Qiyugou gold-bearing breccia pipes, Xiong’ershan region, central China: fluid-inclusion and stable-isotope evidence for an origin from magmatic fluids - Fan, H.; Hu, F.; Wilde, Simon; Yang, K.; Jin, C. (Bellwether Publishing, 2011)
Gold ores of the Qiyugou deposit in the eastern part of the Xiong’ershan region are hosted in breccia pipes within a Mesozoic granitic porphyry. Three stages of hydrothermal alteration activity are recognized within the Qiyugou breccias. The first stage of hydrothermal metasomatism produced extensive K-feldspar alteration. The second stage is associated with deposition of gold and base metal sulphides. The third stage is defined by fine quartz–calcite ^ pyrite veinlets containing minor gold. Four types of fluid inclusions are present in quartz and calcite within the breccia matrix and veins. Type I aresolid(s)-bearing high-salinity fluid inclusions, with homogenization temperatures up to 4208C and high salinities of 31–47 wt%NaCl equivalent. Type II are two-phase, vapourrich fluid inclusions that homogenized between 265 and 4768C, with low to moderate salinities (7.2–19.8 wt% NaCl equivalent). Homogenization of Type III two-phase, liquid-rich fluid inclusions takes place at temperatures between 109 and 2538C, with salinities of 3.9–14.3 wt% NaCl equivalent. Type IV two/three-phase carbonic fluidinclusions are only found in calcite–quartz veins cutting wall rocks in the upper parts of the pipes or in adjacent country rocks, with homogenization temperatures that range from 239 to 3158C and salinities between 9.2 and 12.2 wt% NaCl equivalent. The coexistence of Types I and II in the middle parts of the breccia pipes suggests that these fluid inclusions either resulted from trapping of boiling fluids or represented immiscible fluids, most likely derived from a granitic magma. The fluid history, reflected in the fluidinclusion characteristics, was complex, involving variable amounts of boiling, cooling and mixing in the breccia pipe system. dDH2O values (2101.7 to 260.1‰) and d18OH2O values (0.3–7.5‰) calculated from inclusion water in quartz on the basis of mean-tomaximum fluid inclusion homogenization temperatures are intermediate between magmatic water and surface-derived fluids (meteoric water). Ranges for d34S values of ore sulphides (23.0 to 0.8‰) suggest that sulphur originated directly from a magmatic (mantle) source or indirectly fromleaching/desulphidation of primary magmatic sulphide minerals. The combined fluid-inclusion and stable-isotope data support previousproposals for a genetic relationship between the Qiyugou ores and magmatic fluids.